2011
DOI: 10.1097/mat.0b013e31821c08bc
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Flow Analysis of the Wang-Zwische Double-Lumen Cannula

Abstract: An experimental and numerical analysis was performed for the Wang-Zwische double-lumen cannula (DLC) (Avalon Elite). The aim of this work was to provide insight for future improvement by characterizing the fluid dynamic behavior of the novel catheter with metrics often associated with blood trauma. Pressure and flow distributions were measured on a steady-flow rig using a 50% glycerol-water mixture by imposing a 2 L/min flow rate across the drainage and infusion lumens. The fluid was modeled as Newtonian with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…Experimental and numerical studies of a double-lumen cannula showed that the shear stress was higher in the drainage lumen and regions of turbulence were found at the connection sites to tubing. 5 Additional features (insertion/sidearms). Cannulae inserted into peripheral arteries may nearly occlude the vessel volume and cause downstream ischaemia.…”
Section: Desirable Cannula Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and numerical studies of a double-lumen cannula showed that the shear stress was higher in the drainage lumen and regions of turbulence were found at the connection sites to tubing. 5 Additional features (insertion/sidearms). Cannulae inserted into peripheral arteries may nearly occlude the vessel volume and cause downstream ischaemia.…”
Section: Desirable Cannula Criteriamentioning
confidence: 99%
“…A commonly used approach is to use time-averaged equations (Reynolds-averaged Navier-Stokes equations -RANS) where the velocity is split into a mean and a variable component to allow for efficient numerical solutions. 5 CFD simulations of cannula flow are complex and often only possible using commercial simulation packages, so several authors have developed a simpler expression to estimate the flow-pressure relationship for cannulae. The formalism describes the performance of a cannula with a single number.…”
Section: Cannula Theorymentioning
confidence: 99%
“…14,19,20,21,32,33 The ambulatory pump lung (APL) device features a fully magnetically levitated centrifugal pump integrated into a 0.8m 2 surface area annular fiber bundle 19 having 200 ml/min/m 2 oxygenation efficiency. The compliant thoracic artificial lung (cTAL) features a pumpless device with a 2.4m 2 surface area bundle having ~95 ml/min/m 2 oxygenation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…6 New cannula design with dual lumen and bicaval insertion technique allows for femoralfree single site cannulation with enhanced patient mobility and improved gas exchange efficiency. 7 There has also been advancement in our understanding of patient management on VV-ECMO, including importance of minimal sedation, negative pressure spontaneous breathing, participation in physical therapy, and ambulation. We also have learned that bleeding remains the most frequent ECLS-related complication, and that reduction or even elimination of systemic anticoagulation may be appropriate in certain clinical settings.…”
mentioning
confidence: 99%